Strength and Resilience in Mothers of Children with Cancer: Grit, Hope, and Social Support - Tania Mursalim; Riana Sahrani; Pamela Hendra Heng (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Caring for a child with cancer is a highly stressful psychological experience, particularly for mothers who serve as the primary caregivers. Resilience is understood as the psychological capacity to recover and adapt positively when facing long-term stress. This study aims to examine the effect of grit on resilience among mothers of children with cancer, as well as to analyze the moderating roles of hope and social support. Participants consisted of 216 mothers of children with cancer aged 0–18 years who were currently undergoing or had completed chemotherapy in Indonesia. The instruments used were the Short Grit Scale (Grit-S), Connor-Davidson Resilience Scale (CD-RISC), State Hope Scale (SHS), and Multidimensional Scale of Perceived Social Support (MSPSS). This correlational quantitative study was analyzed using Moderated Regression Analysis (MRA) in JASP. The results showed that grit had a significant positive relationship with resilience (r = 0.289, p < 0.001), as did hope (r = 0.673, p < 0.001) and social support (r = 0.420, p < 0.001). Grit was also positively associated with hope (r = 0.242, p < 0.001) and social support (r = 0.207, p = 0.002). However, the interaction between grit and hope (β = –0.053, t = –0.732, p = 0.465) and between grit and social support (β = –0.098, t = –1.378, p = 0.170) was not significant. These findings emphasize grit as a direct predictor of resilience and encourage the development of personal and social strength based interventions for mothers in the caregiving of children with cancer.